2013
DOI: 10.1016/j.soilbio.2013.01.012
|View full text |Cite
|
Sign up to set email alerts
|

The role of plant-associated bacteria in the mobilization and phytoextraction of trace elements in contaminated soils

Abstract: Phytoextraction makes use of trace element-accumulating plants that concentrate the pollutants in their tissues. Pollutants can be then removed by harvesting plants. The success of phytoextraction depends on trace element availability to the roots and the ability of the plant to intercept, take up, and accumulate trace elements in shoots. Current phytoextraction practises either employ hyperaccumulators or fast-growing high biomass plants; the phytoextraction process may be enhanced by soil amendments that inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
265
0
15

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 597 publications
(286 citation statements)
references
References 166 publications
(126 reference statements)
6
265
0
15
Order By: Relevance
“…Moreover, these bacteria serve a significant function in maintaining the ecological balance of the contaminated soil and could be used for the bioremediation of metal-polluted soil (Hayat et al 2010;Kandeler et al 2000). Numerous studies have reported a few naturally occurring microorganisms with high metal resistance in the rhizosphere that significantly increases the metal uptake in plants and reduces metal toxicity (Ma et al 2011;Sessitsch et al 2013). Furthermore, several other genera were found similar to Arthrobacter, as the dominant genera in group H, and significantly related to heavy metals contents.…”
Section: Bacteria With Potential Resistance To Heavy Metalsmentioning
confidence: 99%
“…Moreover, these bacteria serve a significant function in maintaining the ecological balance of the contaminated soil and could be used for the bioremediation of metal-polluted soil (Hayat et al 2010;Kandeler et al 2000). Numerous studies have reported a few naturally occurring microorganisms with high metal resistance in the rhizosphere that significantly increases the metal uptake in plants and reduces metal toxicity (Ma et al 2011;Sessitsch et al 2013). Furthermore, several other genera were found similar to Arthrobacter, as the dominant genera in group H, and significantly related to heavy metals contents.…”
Section: Bacteria With Potential Resistance To Heavy Metalsmentioning
confidence: 99%
“…The alterations in heavy metal mobilization and its solubility in the rhizosphere soils caused by chemical and/or biological features can have dramatic effect on heavy metal uptake/accumulation in plants (Sessitsch et al, 2013). In this study thus the effects of metal mobilizing RC6b on metal accumulation in roots and shoots of S. plumbizincicola were studied.…”
Section: Influence Of P Myrsinacearum Rc6b On Plant Growth and Metalmentioning
confidence: 99%
“…However, the bioavailability of heavy metals in rhizosphere soils is considered to be an important factor that determines the efficiency of phytoextraction process. Metal tolerant microbes have been frequently reported in the rhizosphere of hyperaccumulators growing in metal polluted soils indicating that these microbes have evolved a heavy metal-tolerance and that they may play significant roles in mobilization or immobilization of heavy metals by excreting various metabolites including organic acids or extracellular polymeric substances (Rajkumar et al, 2012;Prapagdee et al, 2013;Sessitsch et al, 2013). Sedum plumbizincicola is one of the hyperaccumulators (Jiang et al, 2010) which has a remarkable capacity to withstand the metal stress in polluted soils and recent experiments have also demonstrated its potential for heavy metal phytoextraction (Wu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Rubilar et al [36] investigated the ability of white rot fungi (Anthracophyllum discolour and Phanerochaete chrysosporium) to degrade pentachlorophenol to give the best results for the tested consortia of fungi immobilized on wheat grains as lignincellulose material. The test fungi were characterized by rapid growth and high production of lignin degradating enzymes, such as manganese peroxidase and lignin peroxidase, and the effective degradation of contaminants [37].…”
Section: Application Of Biopreparations and Enzymesmentioning
confidence: 99%